Template for Vector data in ISO19139 (multilingual)
The ISO19115 metadata standard is the preferred metadata standard to use. This template is multilingual with a default language set to english. Other language could be used to translate part of the metadata record. Main language is define in metadata section. Other languages could be added to metadata section / locale element.